2023
DOI: 10.1063/5.0157473
|View full text |Cite
|
Sign up to set email alerts
|

Two-phase flow and morphology of the gas–liquid interface for bubbles or droplets in different microchannels

Cheng Chen,
Zefeng Jing,
Chenchen Feng
et al.

Abstract: Two-phase interface fluid, bubble or droplet, has shown broad application potential in oil and gas field development, contaminated soil remediation, and medical treatment. These applications are particularly concerned about the flow characteristics of the two-phase fluid in different channels. Herein, we summarize and analyze the research progress in the flow of bubbles (or droplets) in different channels, mainly including simple, Y-junction/T-junction, and obstructed microchannels. At present, there is no sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…A circular cross-section of the capillary results in approximately cylindrical bubble shapes (Atasi et al, 2018;Zhao et al, 2018), with the formation of a thin liquid film separating the bubble from the capillary wall (Atasi et al, 2018). The variation in width h of this film as a function of bubble velocity has been widely studied and various empirical equations have been proposed (Chen et al, 2023), in particular for elongated bubbles (Atasi et al, 2017;Danov et al, 2021;Jones et al, 2021;Moran et al, 2021). Such work dates back to Taylor (Taylor, 1960), who showed that the ratio h/R c (where R c is the channel radius) asymptotes to 1/3 for Ca → 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A circular cross-section of the capillary results in approximately cylindrical bubble shapes (Atasi et al, 2018;Zhao et al, 2018), with the formation of a thin liquid film separating the bubble from the capillary wall (Atasi et al, 2018). The variation in width h of this film as a function of bubble velocity has been widely studied and various empirical equations have been proposed (Chen et al, 2023), in particular for elongated bubbles (Atasi et al, 2017;Danov et al, 2021;Jones et al, 2021;Moran et al, 2021). Such work dates back to Taylor (Taylor, 1960), who showed that the ratio h/R c (where R c is the channel radius) asymptotes to 1/3 for Ca → 2.…”
Section: Introductionmentioning
confidence: 99%
“…Here Ca is the dimensionless capillary number, Ca = μv b /σ, where μ is the viscosity of the liquid, v b is the bubble velocity, and σ is the surface tension of the gas-liquid interface. Subsequently, more detailed descriptions of the shape of the bubble, and thus the local thickness of the liquid film surrounding it have been obtained, together with respective scaling relations (Atasi et al, 2018;Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%